Healing Diabetic Foot Ulcers: A Comparative Review of Debridement Approaches - Brzyska, Anna; Mozga, Kamila; Karabin, Agnieszka; Bojarska, Małgorzata; Domańska, Natalia (Quality in Sport, 2024)
Introduction and objective: More than 400 million people worldwide suffer from diabetes today. As a result of complications of this disease, diabetic foot ulcers (DFU) develop. Wound treatment consists mainly in cleansing and stimulating tissue healing processes. Depending on the method used, this process may be shorter or longer. Review methods: In March 2023, articles found in the Medline (Pubmed) and Google Scholar databases were selected by using the following keywords: diabetic foot treatment, diabetic foot ulcers (DFU), autolytic debridement, healing DFU. Brief description of the state of knowledge: Each of the methods described in this article has its advantages and disadvantages. Surgical debridement is used in wounds with a large amount of necrotic tissue, but it can be associated with great discomfort for the patient. Clostridial collagenase ointment has been found to be effective in reducing wound area and promoting wound closure but is more expensive. The use of autolytic debridement and larval therapy is associated with a reduction in pro-inflammatory markers, while the use of moist dressings provides a suitable environment for tissue regeneration. Summary: The choice of the appropriate method depends on many factors such as: the patient’s condition, the availability of materials and financial resources. This review paper provides a comprehensive overview of the benefits and drawbacks of different debridement methods for diabetic foot ulcers.